Effects of Exercise Training on the Autophagy-Related Muscular Proteins Expression in Ovariectomized Rats - Zhong, Weiquan; Shi, Xiangrong; Yuan, Honghua; Bu, Huimin; Wu, Lianlian; Wang, Renwei (Frontiers in Physiology, 2019)
Ovariectomy disrupts estrogen production and homeostasis. However, whether exercise training could counteract the ovariectomy-induced influence on muscular autophagy remained elusive. This study examined muscular autophagy in ovariectomized (OVX) rats following 8-week of swimming exercise training (ET). Here, 40 6-month-old female Sprague–Dawley rats were randomly divided into five groups: sham-operated control (Sham), OVX control (OVX), OVX with 60-min ET (OVX-60ET), 90-min ET (OVX-90ET), and 120-min ET (OVX-120ET) for 6 days/week. According to the results of Western blotting, the expression levels of autophagy-related proteins in the OVX gastrocnemius muscle, including mammalian target of rapamycin (mTOR), uncoordinated 51-like kinase 1 (ULK1), Beclin-1, autophagy-related gene (Atg-7), and microtubule-associated protein light chains 3 (LC3) were significantly decreased (all P<0.05), while there was an elevation on the p62 level. ET appreciably mitigated the OVX-induced negative effects on the muscle quality and autophagy pathway, which seemed to be dependent of ET volume. The most optimal outcomes were observed in the OVX-90ET group. The OVX-120 group had adversely augmented catabolic process associated with the gastrocnemius muscle atrophy. In conclusion, the expression levels of autophagy proteins were decreased in ovariectomized rats, which can be appreciably mitigated following 8-week of swimming exercise training.